Retired Officers' Perceptions Regarding Retirement and Old Age Period - Sadullah Hayri Durmaz; Ayşe Canatan (Yaşlı Sorunları Araştırma Derneği, 2024)
Aging is a process that begins with birth and ends with death, which every living being has to experience even if they are different from each other. One of the important turning points in the process is retirement, where individuals who work in order to meet their social, psychological and physical needs throughout the process leave the working life at a certain age within the scope of legally determined rules and become entitled to a certain income without working in return for their past services. In this study, it was aimed to reveal the perceptions of retirement and old age regarding the differences in the economic, social and health situations of the officers of the Land Forces Command who ended their careers, and the sociological effects of retirement on the aging process. 280 retired people from the Turkish Armed Forces Land Forces Command participated in the study. The data were obtained in written form as a result of web-based and face-to-face studies by using the survey form created via closed and open-ended questions. In the mixed method study, "descriptive analysis percentage table" and "coding" methods were used. As a result of the study, it has been found out that retirement is an important turning point in people's lives, retirement is a personal decision within the limits allowed by law, and although the social environment and social relations change with retirement, retirement does not mean loneliness. The concepts of retirement and old age intersect at many points. It has been observed that the fact that retirement at an early age is still possible in Turkey can open new doors for young retirees with the lengthening of hu-man life, and although retirement reminds the society of old age in the sense of aging, this percep-tion is not accepted by retired individuals.